HUBUNGAN KEAKTIFAN DALAM MENGIKUTI KEGIATAN PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) DENGAN KUALITAS HIDUP PENDERITA DIABETES MELLITUS DI WILAYAH KERJA PUSKESMAS ONAN HASANG KABUPATEN TAPANULI UTARA TAHUN 2024 - Pasaribu, Fatimah Azhari S; Dachi, Rahmat Alyakin; Manurung, Hotman; Sipayung, Rosetty (Akupun Tour Publisher, 2024)
Background: Non-Communicable Diseases (NCDs), which are the highest cause of death in Indonesia, include Diabetes Mellitus (DM). Purpose: The aim of the research is to analyze the relationship between activeness in participating in Prolanis activities and the quality of life of DM sufferers. The type of research is quantitative research with a cross-sectional research design approach. The research was conducted in the Onan Hasang Community Health Center working area, North Tapanuli Regency from December 2023 to March 2024. Method: The research population was all Prolanis Program participants who suffered from DM in the Onan Hasang Community Health Center working area, North Tapanuli Regency, namely 103 people. The number of samples was determined using the Slovin formula and the accidental sampling method as many as 82 people. Primary data collection was carried out directly through questionnaires and secondary data was obtained from the Onan Hasang Community Health Center, North Tapanuli Regency. Data analysis was carried out univariate and bivariate. Univariate analysis was carried out to obtain a description of the research variables and bivariate analysis was carried out to test the hypothesis of the relationship between activeness in participating in Prolanis activities and the quality of life of DM sufferers. Hypothesis testing uses the Chi-square statistical test. Disscusion and Conclusion: The research results showed that the activeness in participating in Prolanis activities in the Onan Hasang Community Health Center working area, North Tapanuli Regency was 47.6% not good, 30.5% not good, and 22.0% good. The quality of life of DM sufferers was 67.1% poor and only 32.9% good. The results of hypothesis testing show that there is a relationship between activeness in participating in Prolanis activities and the quality of life of DM sufferers in the Onan Hasang Community Health Center working area, North Tapanuli Regency. This research provides recommendations to further increase participants' active motivation in participating in prolanis activities.